1992
DOI: 10.1159/000108988
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Stroke to the National Health Service in Scotland

Abstract: Scottish National Health Service (NHS) stroke costs have been estimated for 1988 using accounting methods, updating a similar study for 1974. Stroke mortality in Scotland decreased by 36% between 1974 and 1988, but stroke NHS costs decreased only slightly, from 4.7 to 4.3% of total NHS costs. Stroke bed days as a proportion of total bed days rose from 6.4% in 1974 to 7.5% in 1988 and stroke hospital costs were 5.5% of total hospital costs of £4,600 per discharge. This figure is more than twice a preliminary Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 11 publications
1
48
1
1
Order By: Relevance
“…1 It remains the most common cause of disability in adults. Effective acute treatments are proving elusive, and so prevention of stroke is crucial.…”
Section: The Burden Of Strokementioning
confidence: 99%
See 1 more Smart Citation
“…1 It remains the most common cause of disability in adults. Effective acute treatments are proving elusive, and so prevention of stroke is crucial.…”
Section: The Burden Of Strokementioning
confidence: 99%
“…echocardiogram, various blood tests) in the evaluation of patients with TIA and minor stroke for secondary stroke prevention, using local Edinburgh estimates of cost, but this only considered US and IAA, as at that time CTA and MRA were really only experimental. Their recommendations were that the most cost-effective strategy for selecting patients for IAA before endarterectomy, was to (1) ensure that the patient has carotid territory TIAs/minor stroke, (2) ensure that the patient was medically fit and willing to consider carotid IAA and endarterectomy, and (3) perform carotid US before considering IAA. If the US suggested more than about 50% diameter symptomatic internal carotid artery stenosis, then the patient should be considered for IAA.…”
Section: Improving the Assessment Of Diagnostic Testsmentioning
confidence: 99%
“…[1][2][3][4] The majority of these costs and resources are related to hospital inpatient services, with an estimated 80% of stroke patients being admitted to the hospital in inner-city districts. 5 Once admitted, a study of 9 hospitals in 6 European states demonstrated that stroke patients have long lengths of stay relative to other acute conditions.…”
mentioning
confidence: 99%
“…Per-patient costs of stroke in the European Union (EU) have recently been estimated using time horizons from 6 months to the patient's lifetime. [5][6][7][8][9][10][11] Lifetime direct costs of stroke (1996) estimated from a model with two randomized trials of stroke treatment conducted in 13 countries were $82 000. 12 The incidence and costs of stroke are expected to increase substantially as the population of industrialized countries ages in the coming decades.…”
Section: Introductionmentioning
confidence: 99%